One-dimensional uranium(VI) coordination polymers with pyridinecarboxylate ligands. (27th July 2016) - Shepherd, Nicholas D.; Zhang, Yingjie; Karatchevtseva, Inna; Price, Jason R.; Kong, Linggen; Scales, Nicholas; Lumpkin, Gregory R.
Graphical abstract: Four uranyl hydroxyl, oxo- and oxohydroxyl picolinato complexes featuring one-dimensional polymeric structures with different sub-building units have been synthesized via a hydrothermal method to produce picolinate ligand in situ . Abstract: A method to produce picolinate ligand in situ under hydrothermal conditions has been used to synthesize four uranyl hydroxyl, oxo- and oxohydroxyl picolinato complexes. (UO2 )(OH)(Pic) (1 ) (HPic = picolinic acid) contains 7-fold coordinated uranyl hydroxyl dimers linked through μ2 -bridging Pic ligands forming a one-dimensional (1D) polymer. (NH4 )[(UO2 )3 (O)2 (OH)(Pic)2 ] (2 ) consists of 7-fold coordinated uranyl oxohydroxyl trinuclear units linked through both μ2 - and μ3 -Pic ligands forming a 1D polymer. (NH4 )[(UO2 )2 (O)2 (Pic)] (3 ) is constructed with 7-fold coordinated uranyl oxo-dinuclear units linked through oxo- and μ3 -Pic ligands forming a 1D polymer. (NH4 )[(UO2 )4 (O)2 (OH)2 (Pic)2 (INT)]·H2 O (4 ) (HINT = isonicotinic acid) is made of 7-fold coordinated uranyl oxohydroxyl tetranuclear units linked through both Pic and INT ligands forming a 1D polymer. All four polymers are thermal robust to 350 °C. Raman spectroscopy confirmed the presence of uranyl ion and Pic ligand. In addition, red enhanced fluorescence emissions have been observed for both1 and4 . The synthesis method, with the advantage of controlling uranyl hydrolysis and generating ligand in situ, provides a more reliable way to make new coordination polymers of carboxylate ligands with various uranyl hydrolysis species.